THE IMPORTANCE OF UNDERSTANDING AND APPLYING ACCOUNTING SCIENCE TO BUSINESS QUALITY FOR MSME ACTORS - Widia Pangesti Cahya Wardhani; Adelia S.W. Ramadhan; Arzheti Z Lubna; Amanda N.A. Safitri; Ivana Cahyaningrum (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Understanding and applying accounting knowledge has a crucial role in improving business quality for Micro, Small and Medium Enterprises (MSMEs). This research aims to analyze the impact of understanding and doctrine of accounting science on the business quality of MSME actors. This research method involves surveys and data analysis from a number of MSME actors who apply accounting principles in their financial management. The application of accounting science in daily practice helps MSME actors in identifying areas of improvement, mitigating financial risks, and increasing operational efficiency. Additionally, a deep understanding of finance provides a solid foundation for strategic decision making, including capital management, business expansion, and appropriate market targeting. Thus, this research concludes that understanding and applying accounting knowledge has a strategic role in improving the quality of MSME businesses. Efforts to improve financial literacy and provide appropriate support can make a positive contribution to strengthening the MSME sector and driving overall economic growth.